Recoding of an industrial town: bioeconomy hype as a cure from decline?. Issue 1 (2nd January 2021) - Albrecht, Moritz; Kortelainen, Jarmo
ABSTRACT: We study placemaking in Äänekoski, a small Finnish industrial town, by analyzing how the local government utilizes a recent large-scale bioeconomy investment in its attempts to reinvent the town, and how components of place conform to the image building 'script'. We deploy an assemblage concept and study local place as a combination of material and expressive properties, forces of (de-)territorialization, acts of (de-/re-)coding and relations of exteriority. Äänekoski was known as a shrinking mill town before Metsä Group Corporation decided to build a bio-production complex there in 2014. We analyze how the local government attempts to recode the town with the help of bioeconomy-based place branding, town planning and extensive material investments in the townscape. Despite support from the national 'bioconomy hype' and political narratives, several material, expressive and deterritorializing elements (e.g. declining population, unemployment, environmental debates) work against this growth-oriented recoding. The results allow us to draw critical conclusions on small and industrial town image building.